All-optical shaping non-conventional beams based on spatial cross-phase modulation. (20th May 2021) - Pan, Yujia; Lyu, Ziyao; Wang, Changshun
Abstract: All-optical shaping non-conventional beams are demonstrated experimentally by means of spatial cross-phase modulation in the solution of azo-containing material. We report here that an annular beam is able to be generated and manipulated through a light-control-light system, including a focused controlling beam and a parallel controlled beam. As the intensity of controlling light is enhanced above the threshold, the circular dark core turns to a triangular shape gradually. The formation of the polygonal dark core is mainly attributed to the nonaxis-symmetrical thermal convection in the solution sample induced by the heat of controlling light, which breaks the symmetry in vertical direction of the refractive index distribution. In addition, when the controlled light is convergent, a series of concentric rings instead of annular beam is obtained. The formation of two kinds of non-conventional beams is discussed in terms of the conical distribution of the changed reflective index. This all-optical beam shaping reveals potential applications in optical limiting, all-optical modulation, optical trapping, etc.